Wear-resistant member and machine using same
A Cr-based alloy coating with a Nb carbide phase addresses the need for cost-effective wear resistance in mechanical devices, offering performance comparable to Co-based alloys.
Patent Information
- Application Number
- JP2020100223
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-06-09
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-06-09
AI Technical Summary
Existing mechanical devices face challenges in achieving wear resistance, mechanical strength, and cost-effectiveness in sliding, rolling, and valve members, with Co-based alloys being costly and demanding cheaper alternatives without compromising performance.
A Cr-based alloy material with specific composition and microstructure, including a Nb carbide phase, is applied as a coating layer on a metal base material, enhancing wear resistance and reducing costs.
The Cr-based alloy coating provides wear resistance comparable to or exceeding Co-based alloys while being more cost-effective, improving durability and reducing material costs in mechanical devices.
Smart Images

Figure 0007612347000004 
Figure 0007612347000005 
Figure 0007612347000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a wear-resistant member having a metal substrate coated with a coating layer of an alloy material having excellent wear resistance, and to a mechanical device using the same. [Background technology]
[0002] In mechanical devices, sliding, rolling and valve components are very important components that determine the operating accuracy of the mechanical devices and strongly influence the maintenance cycle. The wear resistance of sliding, rolling and valve components (e.g., valve discs and valve seats) is one of the important characteristics that affect the lifespan of these components.
[0003] The simplest method for improving the wear resistance of sliding, rolling and valve members is to form the entire member from a material with excellent wear resistance, but such a simple method is not necessarily the optimal solution from the viewpoint of other properties required for the member (e.g., mechanical strength, toughness, cost).
[0004] On the other hand, there is a method of using a conventional material that is excellent in mechanical strength, toughness, and cost as a base material, and forming a coating layer of a material with excellent wear resistance on the sliding surface, rolling surface, valve body surface, and valve seat surface of the member to produce a sliding member, rolling member, or valve member. Co (cobalt)-based alloy materials such as Stellite (registered trademark) and Tribaloy (TRIBALOY is a registered trademark) have been widely used as materials for such coating layers. However, Co is a material with a relatively high material cost, and there is a strong demand for cheaper materials from the perspective of cost reduction.
[0005] A Cr (chromium) based alloy material is a material that is expected to be less expensive than a Co based alloy material. For example, Patent Document 1 (JP Patent Publication 5-271841) describes a Cr (chromium) based alloy material that contains 30.0 to 48.0 weight % Ni (nickel), 1.5 to 15.0 weight % W (tungsten) and / or 1.0 to 6.5 weight % Mo (molybdenum), with the total of W and Mo being a maximum of 15.0 weight % or less, and optionally containing Fe (iron), Co, C (carbon), B (boron), Al (aluminum), Si (silicon), Nb (niobium) and Ti (titanium). In the case of a powder used for powder overlay welding, the alloy further contains 0.01 to 0.12 weight% of one or more of Al, Y (yttrium), misch metal, Ti, Zr (zirconium), Hf (hafnium) as necessary, and in addition, 0.01 to 0.1 weight% of O (oxygen) as necessary, with the balance being 40 weight% or more of Cr. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 5-271841 Summary of the Invention [Problem to be solved by the invention]
[0007] According to Patent Document 1, it is possible to obtain a highly tough hardfacing material that is excellent in wear resistance, corrosion resistance, and powder build-up weldability. However, in recent years, there has been an increasing demand for improved performance and efficiency of machinery and equipment, and the demands on sliding members, rolling members, and valve members have inevitably become higher than ever before.
[0008] Needless to say, cost reduction is one of the most important issues in the fields of sliding members, rolling members and valve members.
[0009] In view of the above, an object of the present invention is to provide a wear-resistant member that does not contain Co components (i.e., enables lower costs than Co-based alloy materials) and has wear resistance equal to or greater than that of conventional Co-based alloy materials, and a mechanical device using the same. [Means for solving the problem]
[0010] (I) One aspect of the present invention is a wear-resistant member having a coating layer made of a Cr-based alloy material formed on a metal substrate, The coating layer of the Cr-based alloy material has an alloy composition in a surface layer region thereof, More than 40 mass% and not more than 65 mass% Cr; 15% by mass or more and 40% by mass or less of Ni; Fe containing more than 0 mass% and not more than 30 mass%; 5% by mass or more and 16% by mass or less of Nb; 0.1% by mass or more and 0.9% by mass or less of Ti; C of 0.6% by mass or more and 2.5% by mass or less; 2% by mass or less of Mn (manganese); impurities, The mass ratio Ti / Nb of the Nb to the Ti is 0.063 or less; The present invention provides a wear-resistant member characterized by the above-mentioned. In the present invention, the surface region is defined as a region that is 10% of the thickness of the coating layer from the outermost surface of the coating layer.
[0011] In the present invention, the above-mentioned wear-resistant member (I) according to the present invention can be improved or modified as follows. (i) In the coating layer, a Nb carbide phase having a dendritic and granular morphology is precipitated in the surface layer region in an amount of 4 area % or more and 30 area % or less in total. (ii) In the alloy composition, the mass ratio C / Nb of the Nb to the C is 0.11 or more and 0.16 or less, and the mass ratio Ti / Nb is 0.0062 or more. (iii) The coating layer has an alloy composition in the surface region that further includes at least one of 0.1% by mass or more and 5% by mass or less of Cu (copper), 0.1% by mass or more and 1% by mass or less of Si, 0.02% by mass or more and 0.3% by mass or less of Sn (tin), and 0.005% by mass or more and 0.05% by mass or less of Al. (iv) The coating layer has a ferrite phase as a main phase. (v) The thickness of the coating layer is 2 mm or more and 20 mm or less. (vi) The coating layer is a weld overlay layer. (vii) The metal substrate is made of a steel material. (viii) The wear-resistant member is a sliding member, a rolling member or a valve member.
[0012] (II) Another aspect of the present invention is a mechanical device having a sliding member, a rolling member, or a valve member, comprising: The present invention provides a mechanical device, wherein the sliding member, the rolling member or the valve member is the above-mentioned wear-resistant member. Effect of the Invention
[0013] According to the present invention, it is possible to provide a wear-resistant member which can be produced at a lower cost than Co-based alloy materials and has wear resistance equal to or greater than that of conventional Co-based alloy materials, and a machine using the same. [Brief description of the drawings]
[0014] [Figure 1] 1 is a scanning electron microscope (SEM) image showing an example of the microstructure of a Cr-based alloy material of the present invention, which includes a backscattered electron image, a ferrite phase map, an Nb carbide phase map, and an austenite phase map. [Figure 2A] 1 is a schematic cross-sectional view showing a bearing device, which is an example of a mechanical device according to the present invention. [Figure 2B] FIG. 2 is a schematic cross-sectional view showing a fluid device, which is another example of a mechanical device according to the present invention. [Figure 2C]FIG. 4 is a schematic cross-sectional view showing a valve device, which is another example of a mechanical device according to the present invention. [Figure 2D] FIG. 2 is a schematic cross-sectional view showing a machine tool device, which is another example of a mechanical device according to the present invention. [Diagram 3] 1A to 1C are process diagrams showing an example of a method for producing a wear-resistant member according to the present invention. [Figure 4] 4 is an SEM observation image showing an example of the microstructure of a Cr-based alloy material in a test evaluation sample of Example 2, which includes a backscattered electron image, a ferrite phase map, an Nb carbide phase map, and an austenite phase map. [Diagram 5] 4 shows an enlarged backscattered electron image and elemental analysis results of a Cr-based alloy material of a test evaluation sample of Example 2. [Figure 6] 1 is a SEM image showing an example of a cross-sectional microstructure in the vicinity of the surface of an alloy ingot of Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present inventors have conducted extensive research and investigation into the relationship between chemical composition, metal structure, and wear resistance of Cr-based alloy materials that do not contain Co and have Cr as the main component (the component with the highest content), particularly Cr-based alloy materials that contain more than 40 mass% Cr, and have completed the present invention.
[0016] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. The present invention is not limited to the embodiments described herein, and can be appropriately combined with known techniques or improved based on known techniques without departing from the technical concept of the invention.
[0017] The wear-resistant member of the present invention is a metal substrate on which a coating layer of a Cr-based alloy material is formed. There is no particular limitation on the material of the metal substrate, but from the viewpoint of the mechanical strength and cost required for the final wear-resistant member, a steel material can be suitably used. In cases where mechanical strength at high temperatures is more important, a Ni-based alloy material may be used as the material of the metal substrate. There is no particular limitation on the thickness of the coating layer, and it may be appropriately selected depending on the application of the final wear-resistant member, but it is preferable that the thickness is in the range of 2 mm to 20 mm.
[0018] [Chemical composition of Cr-based alloy materials] As described above, the coating layer in the present invention is made of a Cr-based alloy material having Cr as the maximum content component, and is made of an alloy containing impurities, with Ni, Fe, Nb, Ti, and C as essential components other than Cr, Mn as an optional component, and Cu, Si, Sn, and Al as additional optional components. The total content of impurities is preferably 1% by mass or less. In other words, the total of the components intentionally contained is preferably 99% by mass or more.
[0019] In addition, when the metal substrate and the coating layer are heterogeneous alloys (alloys with different compositions), interdiffusion of alloy components may occur near the interface with the metal substrate during the formation process of the coating layer, and the chemical composition near the interface may deviate from the original chemical composition. However, in the formation of the coating layer, the effective diffusion time (the time during which diffusion actually occurs) is usually very short, so the effect of diffusion becomes extremely small as the coating layer thickness is increased (for example, by forming the coating layer in multiple layers). In addition, when discussing wear resistance as in the present invention, the characteristics of the surface layer region of the component are important. For these reasons, in the present invention, the surface layer region of the coating layer (the region from the outermost surface of the coating layer to 10% of the coating layer thickness) is discussed.
[0020] The composition (each component) of the Cr-based alloy coating layer of the present invention will be described below. Note that the remaining components other than the elements described below are impurities that are difficult to control.
[0021] Cr: More than 40% by mass but not more than 65% by mass The Cr component is the maximum content component of the Cr-based alloy material coating layer of the present invention, and has the advantage of being cheaper than Co, making it possible to reduce material costs compared to conventional Co-based alloys. In addition, by making Cr the maximum content component, a passive oxide film is easily formed on the surface of the Cr-based alloy material coating layer, which has the effect of improving corrosion resistance.
[0022] The Cr content is preferably more than 40% by mass, more preferably 45% by mass or more, and even more preferably 50% by mass or more. If the Cr content is 40% by mass or less, the cost reduction effect is weakened and the effect of improving corrosion resistance becomes insufficient. On the other hand, if the Cr content is more than 65% by mass, the melting point of the alloy becomes too high, which deteriorates the manufacturability of the Cr-based alloy material coating layer (increases the manufacturing cost), so the Cr content is preferably 65% by mass or less.
[0023] Ni: 15% by mass or more and 40% by mass or less The Ni component is one of the main components constituting the parent phase (ferrite phase or a mixed phase of ferrite phase and austenite phase) of the Cr-based alloy material coating layer of the present invention, and is a component that contributes to improving the ductility and toughness of the parent phase. The Ni content is preferably lower than the above-mentioned Cr content and higher than the Fe content described below. Specifically, the Ni content is preferably 15 mass% or more, more preferably 20 mass% or more, and even more preferably 25 mass% or more. If the Ni content is less than 15 mass%, the ductility and toughness of the Cr-based alloy material coating layer becomes insufficient. On the other hand, if the Ni content exceeds 40 mass%, the wear resistance of the Cr-based alloy material coating layer becomes insufficient, so the Ni content is preferably 40 mass% or less.
[0024] Fe: More than 0% by mass and 30% by mass or less The Fe component is also one of the main components constituting the parent phase of the Cr-based alloy material coating layer of the present invention, and is a component that contributes to ensuring toughness and hardness. The Fe content is preferably 30 mass% or less, more preferably 20 mass% or less, and even more preferably 17 mass% or less. If the Fe content exceeds 30 mass%, a brittle intermetallic compound σ phase (intermetallic compound phase based on FeCr phase) is likely to be generated, and the ductility and toughness of the Cr-based alloy material coating layer are significantly reduced (so-called σ phase embrittlement). On the other hand, if the Cr-based alloy material coating layer does not contain any Fe component (Fe content is 0 mass%), the wear resistance of the Cr-based alloy material coating layer becomes insufficient. The Fe content in the Cr-based alloy material coating layer is more preferably 10 mass% or more.
[0025] In addition, when a steel material is used as the metal substrate of the Cr-based alloy material coating layer, Fe components may be mixed into the coating layer as the steel substrate melts during the process of forming the coating layer (e.g., overlay welding). Therefore, when it is expected that a considerable amount of Fe components will be mixed in, the Fe content of the welding material (material for forming the coating layer) may be 0 mass%.
[0026] Nb: 5% by mass or more and 16% by mass or less The Nb component is an important component that combines with the C component described later to generate and precipitate an Nb carbide phase (e.g., NbC phase) and contributes to improving the hardening and wear resistance of the Cr-based alloy material coating layer. The Nb component dissolved in the matrix also has the effect of contributing to improving toughness. The Nb content is preferably 5 mass% or more, more preferably 6 mass% or more. If the Nb content is less than 5 mass%, the hardening and wear resistance of the Cr-based alloy material coating layer will be insufficient. On the other hand, the Nb content is preferably 16 mass% or less, more preferably 12 mass% or less. If the Nb content exceeds 16 mass%, the ductility and toughness of the Cr-based alloy material coating layer will be insufficient.
[0027] Furthermore, the mass ratio C / Nb of the Nb content to the C content described below is preferably 0.11 or more and 0.16 or less, more preferably 0.12 or more and 0.14 or less. If the mass ratio C / Nb is less than 0.11, the amount of Nb carbide phase generated is insufficient, and the effect of improving the hardening and wear resistance of the Cr-based alloy coating layer becomes insufficient. If the mass ratio C / Nb exceeds 0.16, the excess C component forms a Cr carbide phase (for example, Cr7C3 phase, Cr 23 C6 phase) is generated and precipitated, which is a factor in reducing the corrosion resistance of the Cr-based alloy coating layer.
[0028] C: 0.6% by mass or more and 2.5% by mass or less The C component is an important component that combines with the above-mentioned Nb component to generate and precipitate the Nb carbide phase, and contributes to the hardening and wear resistance improvement of the Cr-based alloy material coating layer. In addition, even if the C component is dissolved in the matrix, it also has the effect of contributing to the hardening of the Cr-based alloy material coating layer. The C content is preferably 0.6 mass% or more, more preferably 0.7 mass% or more. If the C content is less than 0.6 mass%, the hardening and wear resistance improvement of the Cr-based alloy material coating layer becomes insufficient. On the other hand, the C content is preferably 2.5 mass% or less, more preferably 2 mass% or less, and even more preferably 1.5 mass% or less. If the C content exceeds 2.5 mass%, the Cr carbide phase is excessively generated and precipitated, which is a factor that reduces the corrosion resistance of the Cr-based alloy material coating layer.
[0029] As described above, the mass ratio C / Nb of the C content to the Nb content is preferably 0.11 or more and 0.16 or less, and more preferably 0.12 or more and 0.14 or less.
[0030] Ti: 0.1% by mass or more and 0.9% by mass or less The Ti component combines with oxygen inside the Cr-based alloy coating layer to form fine Ti oxide particles, and is a component that plays a role in capturing and stabilizing excess oxygen that does not contribute to positive effects (so-called deoxidization role). In addition, the dispersed Ti oxide particles function as starting points (seeds) for the generation of Nb carbide phase, and have the effect of contributing to the fine dispersion precipitation of Nb carbide phase. Note that the present invention does not deny the possibility that a part of the Ti component may form carbides (for example, TiC or (Nb,Ti)C).
[0031] The Ti content is preferably 0.1% by mass or more, and more preferably 0.2% by mass or more. If the Ti content is less than 0.1% by mass, the amount of Ti oxide particles produced is insufficient, resulting in insufficient fine dispersion and precipitation of the Nb carbide phase (large, clumpy Nb carbide phase particles tend to precipitate), and as a result, the hardening and wear resistance of the Cr-based alloy material coating layer is insufficient. On the other hand, the Ti content is preferably 0.9% by mass or less, more preferably 0.7% by mass or less, and even more preferably 0.5% by mass or less. If the Ti content exceeds 0.9% by mass, the Ti oxide particles tend to become coarse and tend to be unevenly distributed on the solidification surface of the Cr-based alloy material coating layer together with the Nb carbide phase, which causes a decrease in the corrosion resistance and wear resistance of the Cr-based alloy material coating layer.
[0032] In addition, the mass ratio Ti / Nb of the Ti content to the above-mentioned Nb content is preferably 0.0062 or more and 0.063 or less, more preferably 0.01 or more and 0.05 or less. If the mass ratio Ti / Nb is less than 0.0062, the aggregated Nb carbide phase particles tend to become coarse. If the mass ratio Ti / Nb exceeds 0.063, the Ti content in the Nb carbide phase particles increases and tends to be unevenly distributed on the solidified surface of the Cr-based alloy material coating layer.
[0033] Mn: 2% by mass or less The Mn component is an optional component of the Cr-based alloy coating layer, which combines with sulfur and oxygen to form fine particles of the compound, and plays a role in capturing and stabilizing excess sulfur and oxygen that do not contribute to positive effects (so-called desulfurization and deoxidization role). By capturing and stabilizing sulfur and oxygen, it contributes to improving the corrosion resistance, ductility, and toughness of the Cr-based alloy coating layer.
[0034] Although Mn is not an essential component (its content may be 0 mass%), in order to ensure the effect of Mn inclusion, the Mn content is preferably 0.05 mass% or more. On the other hand, the Mn content is preferably 2 mass% or less, more preferably 1 mass% or less, and even more preferably 0.5 mass% or less. If the Mn content exceeds 2 mass%, it forms coarse particles of sulfides (e.g., MnS), which causes a decrease in the corrosion resistance, ductility, and toughness of the Cr-based alloy coating layer.
[0035] Impurities: Total of 1% by mass or less Representative impurities in the Cr-based alloy coating layer of the present invention include N, O, P, S and Ta. Next, these impurities will be briefly described.
[0036] N: 0.04% by mass or less The N component is an impurity component that reduces the mechanical properties (e.g., ductility, toughness) of the Cr-based alloy coating layer when it combines with the constituents of the Cr-based alloy material to form coarse particles of a nitride phase (e.g., a Cr nitride phase). On the other hand, by controlling the N content to 0.04 mass% or less, it becomes possible to dissolve N in the matrix or form fine particles of the nitride phase, and this also has the effect of improving the mechanical properties (e.g., hardness).
[0037] O: 0.02% by mass or less The O component is an impurity component that reduces the mechanical properties (e.g., ductility, toughness) of the Cr-based alloy coating layer when it combines with the constituents of the Cr-based alloy material to form coarse particles of an oxide phase (e.g., Fe oxide). On the other hand, by controlling the O content to 0.02 mass% or less, it becomes possible to form fine particles of the oxide phase, which also has the effect of improving the mechanical properties (e.g., hardness).
[0038] P: 0.04% by mass or less The P element is an impurity element that easily segregates at the grain boundaries of the Cr-based alloy coating layer and reduces the mechanical properties (e.g., ductility and toughness) and the corrosion resistance of the grain boundaries. By controlling the P content to 0.04 mass% or less, these negative effects can be suppressed.
[0039] S: 0.005% by mass or less The S component is an impurity component that easily combines with the constituents of the Cr-based alloy material to form sulfides (e.g., Fe sulfides) with relatively low melting points, and reduces the mechanical properties and corrosion resistance of the Cr-based alloy material coating layer. By controlling the S content to 0.005 mass% or less, these negative effects can be suppressed.
[0040] Ta: 0.2% by mass or less Ta is one of the components contained in niobium ore (e.g., pyrochlore) and is an impurity component that is easily mixed into Nb raw materials. If the Ta content is 0.2 mass% or less, there is no particular adverse effect. In other words, Ta is not a component that is intentionally contained, but it is a component that is allowed to be contained at 0.2 mass% or less.
[0041] Additional optional ingredients As described above, the Cr-based alloy coating layer of the present invention may further contain at least one of Cu, Si, Sn, and Al as additional optional components. Next, these additional optional components will be briefly described.
[0042] Cu: 0.1% by mass or more and 5% by mass or less The Cu component is one of the optional additional components in the Cr-based alloy material coating layer, and is a component that contributes to improving corrosion resistance. When Cu is contained, its content is preferably 0.1 mass% or more and 5 mass% or less. If the Cu content is less than 0.1 mass%, it is simply difficult to clarify the action and effect based on Cu (no particular inconvenience occurs). On the other hand, if the Cu content exceeds 5 mass%, Cu precipitates are easily generated, which is a factor in reducing the ductility and toughness of the Cr-based alloy material coating layer.
[0043] Si: 0.1% by mass or more and 1% by mass or less The Si component is also one of the optional additional components in the Cr-based alloy material coating layer, and plays a role in deoxidization. When Si is contained, the content is preferably 0.1 mass% or more and 1 mass% or less. If the Si content is less than 0.1 mass%, the action and effect based on Si is difficult to clarify (no particular problems occur). On the other hand, if the Si content exceeds 1 mass%, coarse particles of oxides (e.g., SiO2) are formed, which causes a decrease in the ductility and toughness of the Cr-based alloy material coating layer.
[0044] Sn: 0.02 mass% or more and 0.3 mass% or less The Sn component is also one of the optional additional components in the Cr-based alloy coating layer, and plays a role in strengthening the passive film on the surface of the coating layer, and contributes to improving corrosion resistance (e.g., resistance to chloride ions and acidic corrosive environments). When Sn is contained, its content is preferably 0.02 mass% or more and 0.3 mass% or less. If the Sn content is less than 0.02 mass%, it is simply difficult to clarify the action and effect based on Sn (no particular problems occur). On the other hand, if the Sn content exceeds 0.3 mass%, it causes grain boundary segregation of the Sn component, which becomes a factor in reducing the ductility and toughness of the Cr-based alloy coating layer.
[0045] Al: 0.005 mass% or more and 0.05 mass% or less The Al component is also one of the optional additional components in the Cr-based alloy coating layer, and is a component that contributes to improving the deoxidation effect when combined with Mn and Si. When Al is contained, its content is preferably 0.005 mass% or more and 0.05 mass% or less. If the Al content is less than 0.005 mass%, the action and effect of Al is difficult to clarify (no particular problems occur). On the other hand, if the Al content exceeds 0.05 mass%, coarse particles of oxides and nitrides (e.g., Al2O3 and AlN) are formed, which causes a decrease in the ductility and toughness of the Cr-based alloy coating layer.
[0046] [Microstructure of Cr-based alloy material] Fig. 1 shows an example of the microstructure of the Cr-based alloy material of the present invention, which is observed by a scanning electron microscope (SEM), including a backscattered electron image, a ferrite phase map, a Nb carbide phase map, and an austenite phase map. As shown in Fig. 1, the Cr-based alloy material of the present invention has a matrix composed of a mixed phase of a ferrite phase and an austenite phase, and the Nb carbide phase is dispersed and precipitated in the matrix. When the ratio of each phase is investigated, the ferrite phase is 77.5 area %, the austenite phase is 15.5 area %, and the Nb carbide phase is 7.0 area %.
[0047] A detailed look at the backscattered electron image and the Nb carbide phase map reveals that the Nb carbide phase is mainly precipitated in a dendritic / vein-like form, with granular precipitation in places. In other words, it can be seen that the Nb carbide phase is finely dispersed and precipitated throughout the matrix. It is believed that the Cr-based alloy material of the present invention exhibits excellent wear resistance due to the finely dispersed precipitation of the Nb carbide phase.
[0048] When observing the microstructure of a Cr-based alloy material, the amount of Nb carbide phase precipitation is preferably 4 area% or more and 30 area% or less, more preferably 5 area% or more and 20 area% or less. If the amount of Nb carbide phase precipitation is less than 4 area%, the effect of improving the wear resistance of the Cr-based alloy material is not sufficiently obtained. On the other hand, if the amount of Nb carbide phase precipitation is more than 30 area%, coarse grain Nb carbide phase is likely to precipitate, and the ductility and toughness of the Cr-based alloy material becomes insufficient.
[0049] [Wear-resistant parts and machinery] Fig. 2A is a schematic cross-sectional view showing a bearing device, which is an example of a mechanical device according to the present invention. As shown in Fig. 2A, by using a bearing inner ring 110 and a bearing outer ring 120 (each of which is a type of wear-resistant member according to the present invention) having a rolling surface provided with a Cr-based alloy material coating layer 10 according to the present invention, a bearing device 100 having excellent wear resistance can be obtained. Note that, although Fig. 2A shows a rolling bearing device, the bearing device according to the present invention is not limited to a rolling bearing device and may be a plain bearing device.
[0050] FIG. 2B is a schematic cross-sectional view showing a fluid device, which is another example of a mechanical device according to the present invention. As shown in FIG. 2B, a pump device 200 having excellent wear resistance can be obtained by using a flow path member 210 having a Cr-based alloy material coating layer 10 on its inner surface and an impeller 220 having a Cr-based alloy material coating layer 10 on its outer surface (each of which is a type of wear-resistant member according to the present invention). In the fluid device according to the present invention, there is no particular limitation on the fluid substance, and the fluid substance may be, for example, a gas, a liquid, a powder, or a mixture of two or more of them. In addition, a bearing device 100 may be used as a bearing for the rotating shaft of the impeller 220.
[0051] Fig. 2C is a schematic cross-sectional view showing a valve device, which is another example of a mechanical device according to the present invention. As shown in Fig. 2C, a valve body 310 and a valve seat 320 (each of which is a type of wear-resistant member according to the present invention) having a Cr-based alloy material coating layer 10 on their sliding surfaces are used, thereby making it possible to obtain a valve device 300 having excellent wear resistance. As with the above-mentioned fluid device, there is no particular limitation on the fluid substance to be controlled in the valve device according to the present invention.
[0052] Fig. 2D is a schematic cross-sectional view showing a machine tool device, which is another example of the machine device according to the present invention. As shown in Fig. 2D, by using a die 410 (a type of wear-resistant member according to the present invention) having a Cr-based alloy material coating layer 10 on its working surface (the surface that contacts the processed surface), a forming device 400 with excellent wear resistance can be obtained.
[0053] Although not shown in the figures, other examples of machine tool devices include plastic processing devices using jigs (e.g., rolling rolls, extrusion dies, drawing dies) with a Cr-based alloy material coating layer on the working surface, and machining devices using jigs (e.g., cutting tools) with a Cr-based alloy coating layer on the working surface.
[0054] [Method of manufacturing wear-resistant members] Next, a method for producing the wear resistant member of the present invention will be briefly described.
[0055] Fig. 3 is a process diagram showing an example of a manufacturing method of a wear-resistant member according to the present invention. As shown in Fig. 3, first, an alloy material preparation step S1 is performed to prepare a Cr-based alloy material for forming a coating layer. As long as a Cr-based alloy material capable of forming a desired coating layer can be obtained, there is no particular limitation on the detailed procedure of the alloy material preparation step S1. For example, the alloy material preparation step S1 may include a raw material mixing and melting step S1a in which raw materials are mixed and melted to form a molten metal so as to have a desired alloy composition, and an alloy solidification step S1b in which the molten metal is solidified / solidified to prepare a Cr-based alloy material.
[0056] In order to further reduce the content of impurities in the alloy (to refine the alloy), the raw material mixing and melting step S1a may further include a raw material alloy ingot formation step in which the molten Cr-based alloy is once solidified to form a raw material alloy ingot, followed by a remelting step in which the raw material alloy ingot is remelted to prepare a purified molten metal. There are no particular limitations on the remelting method as long as it can increase the purity of the alloy, but for example, vacuum arc remelting (VAR) can be preferably used.
[0057] There are no particular limitations on the detailed procedure of the alloy solidification step S1b, as long as it produces a Cr-based alloy material in a form suitable for use in the next step, the alloy coating layer formation step S2. For example, casting or atomization methods can be suitably used.
[0058] When preparing a Cr-based alloy material in the shape of a rod, wire, or tape, it is preferable to carry out an elemental alloy ingot formation step in which a Cr-based alloy ingot is formed by casting, followed by an elemental plastic processing step in which the alloy ingot is plastically processed to obtain a Cr-based alloy material of a desired shape. When preparing a powder of the Cr-based alloy material, it is preferable to carry out an elemental atomization step in which a Cr-based alloy powder is formed by an atomization method (for example, a gas atomization method or a centrifugal atomization method in which spherical particles are obtained). After the elemental atomization step, a elemental classification step may be carried out to adjust the particle size to a desired range. The elemental classification step is not an essential step, but is preferable from the viewpoint of improving the usability of the Cr-based alloy powder.
[0059] Next, an alloy coating layer forming step S2 is performed in which a Cr-based alloy material coating layer is formed on a desired location on the metal substrate using the Cr-based alloy material obtained in the alloy material preparation step S1. As long as a desired Cr-based alloy material coating layer can be formed, there is no particular limitation on the method for forming the alloy coating layer, but for example, a build-up welding method or a thermal spraying method can be suitably used.
[0060] There is no particular limitation on the overlay welding method, and conventional methods (e.g., shielded metal arc welding, CO2 welding, MAG (metal active gas) welding, MIG (metal inert gas) welding, TIG (tungsten inert gas) welding, submerged arc welding, PTA (plasma transferred arc) welding) can be used as appropriate. There is also no particular limitation on the thermal spraying method, and conventional methods (e.g., flame spraying, high velocity flame spraying, arc spraying, plasma spraying, cold spray) can be used as appropriate.
[0061] As described above, there is no particular limitation on the material of the metal substrate, and steel materials and Ni-based alloy materials can be appropriately used from the viewpoints of the mechanical strength and cost required for the final wear-resistant member.
[0062] Next, an alloy coating layer shaping process S3 is carried out to finish the Cr-based alloy coating layer formed in the alloy coating layer formation process S2. There is no particular limitation on the shaping process method, and conventional methods (e.g., cutting, grinding, polishing) can be used as appropriate. The alloy coating layer shaping process is not an essential process, but is preferably carried out from the viewpoint of the shape and dimensional accuracy required for the final wear-resistant member. EXAMPLES
[0063] The present disclosure will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0064] [Experiment 1] (Preparation of Examples 1-2 and Comparative Examples 1-3) The raw materials were mixed and melted by high-frequency melting (melting temperature 1500°C or higher, in a reduced pressure Ar atmosphere) to form a molten metal with the nominal alloy composition shown in Table 1. A cylindrical casting (diameter 20 mm × length 50 mm) was then produced by die casting using a copper mold.
[0065] One of the reasons for preparing a cylindrical casting was to investigate the properties of the alloy material itself, while avoiding the risk of alloy composition fluctuations caused by the formation of a coating layer on the metal substrate. The size of the cylindrical casting was selected so that its solidification structure would be equivalent to that of the coating layer.
[0066] [Table 1]
[0067] A-1 and A-2 are Co-based alloy materials that satisfy the alloy composition of the present invention, A-3 is a Co-based alloy material that does not satisfy the alloy composition of the present invention (does not contain Ti), and A-4 and A-5 are commercially available Co-based alloy materials. In Table 1, the content of each component (unit: mass%) is calculated so that the sum of the listed components is 100 mass%. Regarding impurities (N, O, P, S), it was confirmed that the total was 0.1 mass% or less, and then it was included in the content of the main component.
[0068] Plates (15 mm×20 mm×2 mm) were cut out from the cylindrical castings prepared above, and their surfaces were polished to prepare test evaluation samples of Examples 1-2 and Comparative Examples 1-3.
[0069] [Experiment 2] (Investigation of Examples 1-2 and Comparative Examples 1-3) For the test and evaluation samples of Examples 1 and 2 and Comparative Examples 1 to 3 produced in Experiment 1, observation of the microstructure of the alloy material and a test evaluation of the wear resistance were carried out.
[0070] (1) Microstructural Observation The microstructure was observed using a scanning electron microscope-energy dispersive X-ray analyzer SEM-EDX (S-4300SE, manufactured by Hitachi High-Technologies Corporation), and the area ratio of the constituent phases was measured using the GNU Image Editing Program (GIMP, free software). Figure 4 shows an SEM observation image showing an example of the microstructure of the Cr-based alloy material in the test evaluation sample of Example 2, and includes a backscattered electron image, a ferrite phase map, a Nb carbide phase map, and an austenite phase map. Note that the above-mentioned Figure 1 is of the Cr-based alloy material in the test evaluation sample of Example 1.
[0071] The Cr-based alloy material of the test evaluation sample of Example 2 shown in FIG. 4 has a parent phase consisting of a mixed phase of ferrite phase (α phase) and austenite phase (γ phase) as in FIG. 1, and Nb carbide phase is dispersed and precipitated in the parent phase. The Nb carbide phase is mainly precipitated in a dendritic / vein shape, and precipitates in a granular shape in places. The ratio of the constituent phases is 77.4 area % for the ferrite phase, 10.5 area % for the austenite phase, and 12.0 area % for the Nb carbide phase. Example 2 has a higher Nb content than Example 1, and therefore the ratio of the Nb carbide phase is higher.
[0072] Figure 5 shows an enlarged backscattered electron image and elemental analysis results of the Cr-based alloy material of the test evaluation sample of Example 2. As shown in Figure 5, it is found that the granular Nb carbide phase has an average grain size of 10 μm or less. In addition, the Ti component was not detected in the matrix phase (α phase, γ phase) but only in the Nb carbide phase, strongly suggesting that the Ti component serves as the starting point (seed) for the precipitation of the Nb carbide phase.
[0073] In contrast to these Examples 1 and 2, although illustration is omitted, precipitation of coarse grained Nb carbide phase (average grain size exceeds 10 μm) was confirmed in the Cr-based alloy material of the test evaluation sample of Comparative Example 1. In Comparative Example 1, since the alloy material does not contain a Ti component, it is considered that the number of starting points (seeds) for the precipitation of the Nb carbide phase was reduced, causing the Nb carbide phase to become coarse.
[0074] In the Co-based alloy materials of the test evaluation samples of Comparative Examples 2 and 3, although illustration is omitted, since they do not contain an Nb component, no Nb carbide phase was generated or precipitated, and instead, precipitation of a Cr carbide phase was confirmed.
[0075] (2) Testing and evaluation of abrasion resistance As a test of wear resistance, a friction and wear test was performed in which the test evaluation samples were brought into contact with each other and slid back and forth (using a reciprocating friction and wear tester, μ-100N, manufactured by Takachiho Seiki Co., Ltd.) to measure the friction coefficient. The measurement conditions were a surface pressure of 9.9 MPa and a sliding stroke of 15 mm. In addition, the number of scratches (cracks longer than 5 μm) in the wear marks (within a range of 1 cm in the direction perpendicular to the sliding direction) after the friction and wear test was investigated using a SEM.
[0076] Regarding the coefficient of friction, a fluctuation range between 10 and 30 strokes of "within ±0.01" was judged as "excellent," a fluctuation range of "more than ±0.01 within ±0.02" was judged as "pass," and a fluctuation range of "more than ±0.02" was judged as "fail." Regarding scratches in the wear marks after the friction and wear test, a scratch density of "less than 5 pieces / cm" was judged as "excellent," a scratch density of "5 pieces / cm or more but less than 10 pieces / cm" was judged as "pass," and a scratch density of "10 pieces / cm or more" was judged as "fail."
[0077] Furthermore, a Vickers hardness test (based on JIS Z 2244 (2009)) was performed on the test evaluation sample (on the surface not used in the friction and wear test) to measure the Vickers hardness (HV). Seven points were measured (load: 1 kgf, holding time: 10 seconds) using a micro Vickers hardness tester (Shimadzu Corporation, HMV), and the average value of the remaining five points excluding the maximum and minimum values of the seven Vickers hardness values was determined as the Vickers hardness of the sample.
[0078] Regarding the Vickers hardness, "600≦HV" was judged as "excellent," "550≦HV" was judged as "pass," and "HV<550" was judged as "fail."
[0079] For the overall evaluation of wear resistance, a sample was judged as "pass" if the variation range of the friction coefficient, the scratch density in the wear mark, and the Vickers hardness were all "pass" or above, and a sample was judged as "fail" if any one of them was "fail." The results are summarized in Table 2.
[0080] [Table 2]
[0081] As shown in Table 2, in terms of the variation range of the friction coefficient, Examples 1 and 2 are judged as "excellent", Comparative Example 1 is judged as "pass", and Comparative Examples 2 and 3 are judged as "fail". A small variation range of the friction coefficient means that there is little change in the surface state of the friction sliding surface. In addition, it can be seen that Examples 1 and 2 have smaller friction coefficients than Comparative Examples 2 and 3. A small friction coefficient leads to a reduction in friction loss during operation in a mechanical device using that member.
[0082] In terms of the scratch density of the wear marks, Examples 1 and 2 and Comparative Example 2 are judged as "excellent", Comparative Example 1 is judged as "fail", and Comparative Example 3 is judged as "pass". A low scratch density of the wear marks means excellent toughness. In Comparative Example 1, since the precipitation of a coarse-grained Nb carbide phase was confirmed in the microstructural observation, it is considered that the coarse-grained Nb carbide phase was chipped during frictional sliding.
[0083] In terms of Vickers hardness, Examples 1 and 2 are judged as "excellent", Comparative Example 1 is judged as "pass", and Comparative Examples 2 and 3 are judged as "fail". It is confirmed that the Cr-based alloy material of the present invention has a higher hardness than the conventional Co-based alloy material. High Vickers hardness leads to improved wear resistance.
[0084] From these results, Examples 1 and 2 are judged as "pass" in the overall evaluation of abrasion resistance, and Comparative Examples 1 to 3 are judged as "fail."
[0085] [Experiment 3] (Preparation and Investigation of Examples 3 to 4 and Comparative Example 4) Based on the alloy composition of Example 2, Cr-based alloy materials (Examples 3-4 and Comparative Example 4, A-6-A-8) were prepared with varying mass ratios of Ti / Nb in the alloy to investigate the effect of the mass ratio of Ti / Nb. Specifically, the raw materials were mixed to obtain the nominal alloy composition shown in Table 3, and an alloy ingot (diameter 34 mm, approximately 50 g) was produced by arc melting (in a reduced pressure Ar atmosphere) on a water-cooled copper hearth. At this time, the alloy ingot was remelted six times to homogenize it.
[0086] [Table 3]
[0087] The produced alloy ingots of Examples 3 and 4 and Comparative Example 4 were cut and polished to prepare test evaluation samples, and the microstructures were observed in the same manner as in Experiment 2.
[0088] Although not shown in the figures, the Cr-based alloy materials of Examples 3 and 4 tended to have an increased number of precipitated granular Nb carbide phases as the mass ratio Ti / Nb increased compared to the Cr-based alloy material of Example 2. However, a microstructure similar to that of the Cr-based alloy material of Example 2 (see FIG. 4) was basically observed.
[0089] On the other hand, the microstructure of the Cr-based alloy material of Comparative Example 4 was different from those of Examples 2 to 4. Fig. 6 is an SEM observation image showing an example of the cross-sectional microstructure near the surface of the alloy ingot of Comparative Example 4. As shown in Fig. 6, it can be seen that the coarse-grained Nb carbide phase (average grain size exceeding 10 µm) is unevenly distributed in the surface region (final solidification region) of the alloy ingot, and the amount of precipitation of the Nb carbide phase is reduced in the inner region of the alloy ingot.
[0090] The cause of such a fine structure is thought to be that the specific gravity of the Nb carbide phase particles decreases due to an increase in the Ti content in the Nb carbide phase particles, and the Nb carbide phase particles float up (are pushed out to the final solidification region) during solidification of the parent phase. This type of structure is not preferable because it makes it difficult to control the precipitation amount of the Nb carbide phase in the final Cr-based alloy material coating layer (i.e., the inner region of the Cr-based alloy material coating layer) because the Nb carbide phase particles near the surface are scraped off when performing surface grinding to finish and shape the Cr-based alloy material coating layer.
[0091] The above-mentioned embodiments and examples have been described to aid in understanding the present invention, and the present invention is not limited to the specific configurations described. For example, it is possible to replace a part of the configuration of the embodiments with a configuration according to the technical common sense of a person skilled in the art, and it is also possible to add a configuration according to the technical common sense of a person skilled in the art to the configuration of the embodiments. In other words, it is possible to delete, replace, or add a part of the configuration of the embodiments and examples of the present specification without departing from the technical idea of the invention. [Explanation of symbols]
[0092] 10…Cr-based alloy coating layer, 100... bearing device, 110... bearing inner ring, 120... bearing outer ring, 200: pump device; 210: flow path member; 220: impeller; 300... valve device, 310... valve body, 320... valve seat, 400...molding processing equipment, 410...mold.
Claims
1. A wear-resistant member having a coating layer made of a Cr-based alloy material formed on a metal substrate, When a region of the coating layer that is 10% of the thickness of the coating layer from the outermost surface of the coating layer is referred to as a surface region, The alloy composition in the surface region of the coating layer is More than 40 mass% and not more than 65 mass% Cr; 15% by mass or more and 40% by mass or less of Ni; Fe of more than 0 mass% and 30 mass% or less; 5% by mass or more and 16% by mass or less of Nb; 0.1% by mass or more and 0.9% by mass or less of Ti; C of 0.6% by mass or more and 2.5% by mass or less; 2% by mass or less of Mn; 5% by mass or less of Cu; 1% by mass or less of Si; 0.3% by mass or less of Sn; 0.05% by mass or less of Al; and 1% by weight or less of impurities; The mass ratio C / Nb of the Nb to the C is 0.11 or more and 0.16 or less, The mass ratio Ti / Nb of the Nb to the Ti is 0.0062 or more and 0.063 or less; A wear-resistant member characterized by:
2. The wear-resistant member according to claim 1, A wear-resistant member, characterized in that the surface layer region is precipitated with a Nb carbide phase having a dendritic and granular morphology in an amount of 4 area % or more and 30 area % or less in total.
3. The wear-resistant member according to claim 1 or 2, The wear-resistant member is characterized in that the surface layer region has a ferrite phase as a main phase.
4. The wear resistant member according to any one of claims 1 to 3, A wear-resistant member, wherein the coating layer has a thickness of 2 mm or more and 20 mm or less.
5. The wear resistant member according to any one of claims 1 to 4, 13. A wear-resistant member, wherein the coating layer is a welded build-up layer.
6. The wear resistant member according to any one of claims 1 to 5, The wear-resistant member is characterized in that the metal substrate is made of a steel material.
7. The wear resistant member according to any one of claims 1 to 6, A wear-resistant member which is a sliding member, a rolling member or a valve member.
8. A mechanical device having a sliding member, a rolling member, or a valve member, A mechanical device, wherein the sliding member, the rolling member, or the valve member is the wear-resistant member according to any one of claims 1 to 6.
Citation Information
Patent Citations
High chromium alloy with excellent corrosion resistance against mixture of nitric and hydrofluoric acids
JP1978079711A
High toughness chromium based alloy for hard facing, its powder and engine valve for automobile with the alloy built-up
JP1993271841A
Valve for nuclear power plant
JP2016033451A
Cr-BASED TWO-PHASE ALLOY AND PRODUCT THEREOF
WO2017169056A1
Cr-Ni BASED ALLOY, RAPIDLY SOLIDIFIED MOLDED BODY MADE OF Cr-Ni BASED ALLOY, ALLOY POWDER, POWDER METALLURGY MOLDED BODY, CAST MOLDED BODY, PRODUCTION METHOD FOR Cr-Ni BASED ALLOY AND MECHANICAL EQUIPMENT USING Cr-Ni BASED ALLOY, AND PIPING MEMBER
WO2019189531A1